2012
DOI: 10.2165/11630920-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes of Pregnancy in Women Exposed to the New Macrolides in the First Trimester

Abstract: This study, in agreement with earlier smaller studies, suggests that the new macrolides do not pose a significantly increased risk of major congenital malformations or cardiac malformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 15 publications
2
18
0
4
Order By: Relevance
“…Four studies using data from teratology information services did not find an association between the use of macrolides and spontaneous abortion. [1][2][3][4] In contrast, a Danish study based on data from a prescription database found an increased risk of spontaneous abortion associated with the use of clarithromycin. 5 Three studies using data from teratology information services failed to show a link between the use of quinolones and the risk of spontaneous abortion, [6][7][8] and an early Medicaid study showed an association with the use of metronidazole.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Four studies using data from teratology information services did not find an association between the use of macrolides and spontaneous abortion. [1][2][3][4] In contrast, a Danish study based on data from a prescription database found an increased risk of spontaneous abortion associated with the use of clarithromycin. 5 Three studies using data from teratology information services failed to show a link between the use of quinolones and the risk of spontaneous abortion, [6][7][8] and an early Medicaid study showed an association with the use of metronidazole.…”
mentioning
confidence: 94%
“…9 However, the studies were all limited by either small samples, or recall or indication bias. [1][2][3][4][5][6][7][8][9] Studies of the risk of spontaneous abortion associated with tetracyclines and nitrofurantoin are lacking.…”
mentioning
confidence: 99%
“…In contrast, a widely publicized Swedish study reported increased risk of cardiovascular malformations, leading several Scandinavian countries to avoid prescribing the drug to pregnant women (14). Data concerning the fetal safety of clarithromycin, azithromycin, and roxithromycin have been limited but failed to show increased fetal risks (15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Risiko for spontanabort etter antibiotikabruk ble undersøkt i syv av studiene (9,14,15,17,21,29). I de tre danske der man fant signifikant økt risiko for spontanabort, var det ikke kontrollert for infeksjon etter bruk av en rekke antibiotika (klaritromycin, pivmecillinam, sulfametizol, trimetoprim).…”
Section: Trinnunclassified
“…Gravide har noen ganger en urealistisk oppfatning av hvor farlig legemidler er for fosteret, det gjelder også trygge antibiotika som penicilliner (41). Enkelte velger å ta abort på grunn av frykt for å få et barn med misdannelser (14,15 …”
Section: Trinnunclassified